2007
DOI: 10.1681/asn.2006080821
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Removal of Immunoglobulin Free Light Chains by Hemodialysis for Multiple Myeloma

Abstract: Of patients with newly diagnosed multiple myeloma, approximately 10% have dialysis-dependent acute renal failure, with cast nephropathy, caused by monoclonal free light chains (FLC). Of these, 80 to 90% require long-term renal replacement therapy. Early treatment by plasma exchange reduces serum FLC concentrations, but randomized, controlled trials have shown no evidence of renal recovery. This outcome can be explained by the low efficiency of the procedure. A model of FLC production, distribution, and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
140
2
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(153 citation statements)
references
References 28 publications
6
140
2
5
Order By: Relevance
“…The dependence of renal response on light chain levels was only present in patients with cast nephropathy. A recent analysis suggested that superior light chain removal could be achieved using a "high cutoff" hemodialysis membrane, not yet available in the United States (38).…”
Section: Myeloma Cast Nephropathymentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence of renal response on light chain levels was only present in patients with cast nephropathy. A recent analysis suggested that superior light chain removal could be achieved using a "high cutoff" hemodialysis membrane, not yet available in the United States (38).…”
Section: Myeloma Cast Nephropathymentioning
confidence: 99%
“…Researchers recently identified soluble urokinase receptor in the plasma of patients with recurrent FSGS, capable of inducing profound albuminuria when incubated with isolated rat glomeruli (38,39). It may be causative in the proteinuria through a mechanism that includes lipid-dependent activation of the a5b3 integrin (44,45).…”
Section: Recurrent Fsgsmentioning
confidence: 99%
“…A small study investigating hemodialysis with a protein-leaking dialyzer indicated that large reductions in the concentration of serum-free light chains could be obtained. 47 The same group also investigated the use of high cutoff hemodialysis in combination with systemic treatments and found that 13 of 18 patients with renal failure became dialysisindependent. 48 Renal recovery was also associated with improved survival (Po0.02).…”
Section: Supportive Carementioning
confidence: 99%
“…Therefore, it is crucial to identify MM-related renal diseases as early as possible to initiate adequate treatment. Potential therapeutic strategies for improving renal function are chemotherapy, with or without subsequent autologous stem cell transplantation, and extended dialysis with protein-leaking dialyzers (Hutchison et al, 2007). According to in vitro and in vivo data (Arimura et al, 2006), the application of the pituitary adenylate cyclase-activating polypeptide could be a promising alternative in the future.…”
mentioning
confidence: 99%